2D-Bi2MoO6/2D-g-C3N4 nanosheet heterojunction composite: synthesis and enhanced visible light photocatalytic mechanism. (21st December 2018) - Guo, Ruonan; Zhang, Xinyi; Li, Bo; Zhang, Huixuan; Gou, Jianfeng; Cheng, Xiuwen
Abstract: In this study, a novel 2D Bi2 MoO6 nanosheet/2D g-C3 N4 nanosheet heterojunction composite was fabricated through a hydrothermal strategy. Afterwards, physicochemical properties of the composite were systematically detected by a series of measurements. In addition, photocatalytic activity was evaluated by the degradation of rhodamine B, methylene blue, Amido black 10B and malachite green. The results showed that Bi2 MoO6 /g-C3 N4 possessed higher photocatalytic efficiency than that of the pristine Bi2 MoO6 and g-C3 N4 sample under visible irradiation. This phenomenon could be attributed to the combination of Bi2 MoO6 and g-C3 N4 as well as the unique 2D/2D heterostructure. Also, the as-fabricated Bi2 MoO6 /g-C3 N4 composite possessed higher surface area, narrower bandgap energy, larger electron transport capability and longer charge carrier lifetime. Furthermore, the enhanced visible-light-driven photocatalytic mechanism was proposed and confirmed, which was mainly ascribed to the Z-scheme structure. That is, the photogenerated electrons ( e − ) in the conduction band (CB) of Bi2 MoO6 and photogenerated holes ( h + ) in the valence band (VB) of g-C3 N4 could combine with each other quickly, so that the e − in the CB of g-C3 N4 and h + in the VB of Bi2 MoO6 participated in reduction and oxidation reactions, respectively. Also, this composite exhibited superior physicochemical stability. Hence, it could be applied in advanced wastewater treatment.